The Lead Exposure among Lead Workers: An Epidemiological Study from West Turkey - M Tozun (Iranian Journal of Public Health, 2009)
Background: This study has been conducted on workers from several workplaces where materials containing lead are used during December 2006-April 2007 in Eskişehir, a city of the Middle Anatolian Region of Turkey. Methods: The study and control groups were occured with 403, and 97 men, respectively. After each interview with the individuals, their blood pressures (BP) and complete blood counts (CBC) were measured. The blood lead level (BLL) of 10 μg/dL was accepted as cut off level for high BLL. In statistical analyses, Chi-square test (x2), Fisher's exact test, Student t-test, Kolmogorov-Smirnov Z test, and Logistic regression analysis were applied. Results: The mean age was 35.55±9.00 yr (min=18, max= 54) in study group. The prevalence of high BLL was 10.2% (n= 41) in study group. The working on smeltery, and the working on polyvynil chloride product, and history of lead poisoning are important risk factors for high BLL (for each one P< 0.05). Conclusion: This study indicated several precautions and steps to be taken for better protection from lead poisoning: considering workplace medicine more seriously and particularly planning special health programs in order to raise awareness among workers for using protective gear/wear and applying routine hygienic habits, and improving the preventive measures for workplaces, and providing technical equipment for routine MAC measurements in workplaces, and increasing the legal liability and sanctions.